The Impact of National Intellectual Capital (NIC) on Financial Inclusion (FI): Evidence from Emerging Markets - Maimoona Sadiq; Hamid Ullah (Dialogue Social Science Review (DSSR), 2025)
The purpose of this study is to examine the impact of national intellectual capital (NIC) on Financial Inclusion (FI). For this purpose, 2SLS methodology was employed to generate novel indices for NIC and financial inclusion and then the impact was observed. The findings suggests that national intellectual capital significantly enhances financial inclusion specifically affecting the availability and accessibility perspectives. The observed control variables of the study indicated that GDP positively impacts financial inclusion, however inflation negatively affects affordability and penetration perspectives of financial inclusion. Gender inequality, population density, urbanization and gender equality has been considered an essential indicator of financial inclusion with geographical and income disparities persuading access to financial services. This research emphasizes the significance of NIC in fostering sustainable development and evidence-based strategies to improve financial inclusion exclusively in emerging nations. To augment financial inclusion, legislators are encouraged to prioritize factors like gender equality, urbanization and inflation control while regulators should develop robust strategies and frameworks to support the underserved.